2016
DOI: 10.3382/ps/pew224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-hatch brooding temperature on broiler behavior, welfare, and growth

Abstract: An elevated brooding temperature during the first wk post hatch of broilers may potentially increase activity levels and reduce welfare problems in terms of non- and slow-starters, lameness, and contact dermatitis. The effects of an elevated brooding temperature the first 7 d post hatch on behavior, welfare, and growth of Ross 308 broilers were investigated. Groups of 28 broilers (14 males and 14 females) were distributed in a balanced way according to their hatching weight (below or above mean), the age of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
4
0
3
Order By: Relevance
“…For the first seven days, it was also noted whether the chick was found dead (and the presumed cause of death) or had been culled (and reason for culling, e.g., non-starter, deformities, etc.). To determine whether the chick had accessed feed and/or water, the crop content was assessed by external palpation using a 4-point scale ( Henriksen et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the first seven days, it was also noted whether the chick was found dead (and the presumed cause of death) or had been culled (and reason for culling, e.g., non-starter, deformities, etc.). To determine whether the chick had accessed feed and/or water, the crop content was assessed by external palpation using a 4-point scale ( Henriksen et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Birds are expected to reach slaughter weight in 5-6 weeks and in order to maximise growth they must not waste energy keeping warm or cool. Inappropriate environmental conditions may also increase the risk of disease ((Pan et al 2005), with the first week being particularly important for bird growth and welfare in this regard (Henriksen et al 2016). Environmental sensors placed in the house to record factors such as temperature, humidity, air speed and ammonia levels can only record in set locations and there is often a discrepancy in environmental conditions between human and chicken head height (Miles et al 2008, Wheeler et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…This research only considered the assessment information on the farm, but it should also cover the production period on the farm and the period at the end of life, including transport and slaughter [17]. Many studies have suggested that animal welfare can be improved in terms of post-hatch brooding temperature at hatcheries, stunning broilers in the slaughterhouse, and supplying organic acid during transportation [38], and measures for slaughter [39]. These are also areas of future research with the hope of systematically improving animal Welfare Quality index scores.…”
Section: Discussionmentioning
confidence: 99%